Comparative study of design ideas development approaches in fashion design course / Prinses Saliang - Saliang, Prinses (Universiti Teknologi MARA, 2018)
This study compared three design ideas development approaches implemented in fashion design course through students’ artworks and responses. It was observed that various design approaches were implemented within the same course and discipline, has resulting inconsistent outcomes in students’ artworks. Creativity may be stimulated in various approaches, nonetheless, the outcome of this study will further justify the ideal approach in fashion design ideas development process, depending on variable of requirements stated on design brief. Understanding the strengths of each approach will be beneficial to lecturers and students in enhancing design process and body of knowledge even further as a whole.